Design guidelines for recycling of rotating machines - Ismail, Daut; Anayet Karim; Dina Maizana, Maiz Ahmad; Haziah, Abd Hamid; Samila, Mat Zali (International Association of Science and Technology for Development (IASTED), 2008)
Organized by International Association of Science and Technology for Development (IASTED), 2nd - 4th April 2007 at Phuket, Thailand.